Working paper. Beef cattle production program. CIAT - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1975)
The purpose of this paper is to make an analysis of the nature and severity of beef cattle production constraints in the lowland tropics of Latin America that might be resolved or ameliorated through research in CIAT or elsewhere, and make recommendations on the nature and scope of future CIAT Beef Cattle Program.